THE EFFECT OF QUANTUM ENTANGLEMENT TO THE POWER SPECTRUM AND ENTANGLEMENT ENTROPY IN EARLY UNIVERSE - Gst. Ag. Anom Trenggana D., I
In this research, will be studied the theoretical application of quantum entanglement phenomena in early universes. To study about this phenomena, two method will be used. In the first method will be calculated the power spectrum of some entangled state from initial condition of the universes. In the second method will be calculated entanglement entropy by using Ryu-Takayanagi formula, with assumption that observable system is in the space of 3-dimension AdS with dS boundary. We got for the first method, generaly the magnitude of the power spectrum is not affected by entangled state from n-universes. The magnitude of the power spectrum is more affected by how close the probability of the state to the state of one particle creation. If the entangled state is in W state, more and more the amount of the universes are entangled, the less power spectrum that is produced, with the minimum value is the value of the vacum state. If the state is in GHZ state the power spectrum will be the same for every n-universes that are entangled, with the value is two times the value of vacum state and for the Bell’s state the value of the power spectrum is one of two times value of the vacum state or has the same value with the vacum state. For the second method we got that when t < 1 the magnitude of entanglement entropy will be increased quadratically as long as time goes to 1. When the time is 1 < t < tm the entanglement entropy will be increased linierlly up until the entanglement entropy reach his maximum value at t = tm . After that,the entanglement entropy will be decreased significantly.